The Role of Women and Children Service Units in Preventing Sexual Violence Against Children in Purwakarta Police Jurisdictions - Ojesa Wileta Panggabean (Advances in Police Science Research Journal, 2021)
The increase in the number of cases of sexual violence with child victims in Purwakarta District since 2014– 2017 is the background for this research. The PPA unit is part of the National Police assigned to handle cases of sexual violence against children. The purpose of this study was to determine the factors that influence sexual violence and the role of the PPA unit in preventing sexual violence against children. This study uses a qualitative approach with field research methods. Using interview, observation and document study techniques for data collection. The theory used as an analysis knife is role theory, action theory and crime prevention theory. The causes of sexual violence are influenced by the social system, cultural system, and personality system of the perpetrator and the child. So that in order to minimize these causative factors, the PPA Unit is given responsibility in accordance with the applicable legal regulations. The role of the PPA unit, namely implementing legal protection, law enforcement as well as cooperation and coordination with agencies related to the protection of women and children, is still not optimal. Due to the inconsistency of outreach and outreach activities carried out together with the P2TP2A Purwakarta institution, as well as law enforcement that has not complied with the prevailing laws and regulations so as not to have a deterrent effect on the perpetrators The conclusion of this study is that sexual violence against children can be viewed from the social, cultural and personality systems of the perpetrator and the child. The role of the PPA Unit is still not optimal, both from the role of legal protection, the role of law enforcement and coordination and cooperation. So the suggestion that can be given is that it is necessary to instill religious, moral, and legal values ​​in the community, so as to minimize the factors that influence sexual violence against children. Furthermore, it is necessary to coordinate with other related institutions in a more structured manner in carrying out activities aimed at preventing sexual violence such as socialization and counseling, as well as law enforcement related to cases of sexual violence against children, must be adjusted to the applicable legal regulations.